Increasing rates of anterior cruciate ligament reconstruction in young Australians, 2000–2015. Issue 8 (23rd April 2018) - Zbrojkiewicz, David; Vertullo, Christopher; Grayson, Jane E
Abstract: Objectives: To investigate the incidence and demographic features of anterior cruciate ligament (ACL) reconstructions in Australia by age and sex, and to determine whether the incidence has changed during the past 15 years. Design and setting: Descriptive epidemiological analysis of longitudinal data on ACL reconstructions (July 2000 – June 2015) in the National Hospital Morbidity Database. Main outcome measures: Population ACL reconstruction rates, by age group and sex. Results: 197 557 primary ACL reconstructions were performed during the study period; the annual incidence increased by 43% (from 54.0 to 77.4 per 100 000 population), and by 74% among those under 25 years of age (from 52.6 to 91.4 per 100 000 population). In males, the peak incidence in 2014–15 was for 20–24‐year‐olds (283 per 100 000 population); for females, it was for 15–19‐year‐olds (164 per 100 000 population). Annual growth in incidence was greatest in the 5–14‐year‐old age group (boys, 7.7%; girls, 8.8%). Direct hospital costs of ACL reconstruction surgery in 2014–15 were estimated to be 142 million. The annual incidence of revision ACL reconstructions increased from 2.49 (2000–01) to 5.65 per 100 000 population (2014–15), or by 5.6% per year; revisions as a proportion of all ACL reconstruction increased from 4.4% to 6.8%. Conclusions: The increasing incidence of ACL reconstructions in young Australians over 15 years is worrying. The individuals at greatest risk are men aged 20–24 years and women aged 15–19 years; the rate of reconstruction is increasing most rapidly among those aged 5–14 years. Revision rates are increasing more rapidly than those of primary reconstructions.